Associations between supportive leadership behavior and the costs of absenteeism and presenteeism: an epidemiological and economic approach - Schmid, Johannes A.; Jarczok, Marc N.; Sonntag, Diana; Herr, Raphael; Fischer, Joachim E.; Schmidt, Burkhard (Journal of occupational and environmental medicine, 2017)
This study investigates associations between supportive leadership behavior (SLB) and presenteeism/absenteeism, and estimates related costs. Cross-sectional data from a German industrial sample (n = 17,060) assessing SLB and presenteeism/absenteeism were used. Adjusted interval regressions were performed. The study population was split into tertiles with respect to SLB, and minimum and maximum costs for each tertile were estimated on the basis of national industry averages. Low SLB was associated with higher presenteeism [−0.31, 95% confidence interval (95% CI) −0.33 to −0.28)] and absenteeism (−0.36, 95% CI −0.40 to −0.32). Compared with high SLB, the costs of low SLB for absenteeism are between 534.54 and 1675.16 Euro higher per person and year. For presenteeism, this difference ranges between 63.76 and 433.7 Euro. SLB has the potential to reduce absenteeism, presenteeism, and associated costs. To contribute to workforce health, productivity, and efficiency, SLB merits being fostered by corporate policy.